A revision of the Anthaxia (Haplanthaxia) schah Abeille de Perrin, 1904 species-group, with description of two new species from Iran (Coleoptera: Buprestidae: Anthaxiini) - Baiocchi, Daniele (Zootaxa, 2015)
Two new species of Anthaxia Eschscholtz, 1829 endemic to Iran, Anthaxia (Haplanthaxia) cadusiana sp. nov. and A. (H.) elamita sp. nov., are described and compared to their most similar species. The A. (H.) schah Abeille de Perrin, 1904 species-group is proposed and revised, and lectotypes for A. (H.) schah Abeille de Perrin, 1904 and A. (H.) wethloi Obenberger, 1940 are designated. All species of the new species-group are illustrated, including type specimens. A short definition of the new species-group and a key to its species are given, together with data on the distribution, bionomy and taxonomic position for each of the species that compose it.